2016
DOI: 10.1080/14760584.2016.1198259
|View full text |Cite
|
Sign up to set email alerts
|

Questions regarding the safety and duration of immunity following live yellow fever vaccination

Abstract: Introduction The World Health Organization (WHO) and other health agencies have concluded that yellow fever booster vaccination is unnecessary since a single dose of vaccine confers lifelong immunity. Areas Covered We reviewed the clinical studies cited by health authorities in their investigation of both the safety profile and duration of immunity for the YFV-17D vaccine and examined the position that booster vaccination is no longer needed. We found that antiviral immunity may be lost in 1-in-3 to 1-in-5 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 101 publications
(239 reference statements)
3
57
1
2
Order By: Relevance
“…Serious adverse events (SAE) including deaths occur following administration of YF vaccine [27,[94][95][96], and the frequency of vaccine-related SAEs for YF vaccine is comparable to the rate of vaccine-associated paralytic poliomyelitis with oral polio vaccine [97,98]. In addition, because YF vaccine is a live-attenuated vaccine produced in eggs, there are several contraindications and precautions to its administration [99].…”
Section: Safety Profile Of Yellow Fever Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious adverse events (SAE) including deaths occur following administration of YF vaccine [27,[94][95][96], and the frequency of vaccine-related SAEs for YF vaccine is comparable to the rate of vaccine-associated paralytic poliomyelitis with oral polio vaccine [97,98]. In addition, because YF vaccine is a live-attenuated vaccine produced in eggs, there are several contraindications and precautions to its administration [99].…”
Section: Safety Profile Of Yellow Fever Vaccinesmentioning
confidence: 99%
“…A review of U.S. Vaccine Adverse Event Reporting System (VAERS) data from 2007-2013 found 3.8 SAEs per 100,000 vaccine doses [94], while a review of passive surveillance data from several non-endemic countries found rates ranging from 1.3 to 5.1 SAE per 100,000 vaccine doses [98]. The rate is known to increase with age such that 60-69-year old vaccine recipients had a rate of 6.5 SAEs per 100,000 doses while those over 70 years old had a rate of 10.3 [94].…”
Section: Safety Profile Of Yellow Fever Vaccinesmentioning
confidence: 99%
“…A single-dose vaccination has been implemented since April 2017, however due to conflicting results on immunity in long-term YFV studies it is still under debate among vaccination experts [6,[18][19][20][21].…”
Section: Yellow Fever: Disease and Vaccinementioning
confidence: 99%
“…Studies published to date (WHO, ACIP, and CDC) have shown that approximately 88% of healthy individuals remain seropositive for more than ten years after the YFV [20]. On the other hand, Brazilian studies have demonstrated a fall in protection after 5-10 years in some groups [6,24].…”
Section: Yellow Fever Vaccine: Assessment Of the Immunogenicitymentioning
confidence: 99%
“…Conversely, there is evidence of waning immunity in vaccinees in non-endemic areas, independent of exposure to related flaviviruses [27]. Additionally, it has been suggested that vaccinees who clear the virus without prolonged presentation of antigen to T cells and B cells may not mount a strong immune response, thereby failing to induce lifelong immunity [33]. …”
Section: Immune Response To Vaccination and Long-term Immunitymentioning
confidence: 99%